Gate voltage control of the Rashba effect in a p-type GaSb quantum well and application in a complementary device - Park, Youn Ho; Shin, Sang-Hoon; Song, Jin Dong; Chang, Joonyeon; Han, Suk Hee; Choi, Heon-Jin; Koo, Hyun Cheol (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The gate voltage dependence of the Rashba effect in a p-type quantum well was investigated by using Shubnikov-de Haas measurements. The GaSb-based p-type quantum well has a large Rashba spin-orbit interaction parameter of 1.71 x 10(-11) eVm for a zero gate voltage and exhibits gate controllability. We also propose a complementary logic device using n- and p-type spin transistors that simultaneously utilize charge and spin currents to improve the signal margin. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: 2-DIMENSIONAL ELECTRON-GAS; EFFECTIVE-MASS; SPIN; FIELD